1991
DOI: 10.1002/ijc.2910490112
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of 3 european case‐control studies of epithelial ovarian cancer: III. Oral contraceptive use

Abstract: The relationship between use of oral contraceptives (OCs) and other contraceptive methods and the risk of ovarian cancer was examined in a combined analysis of 3 hospital-based case-control studies conducted in Italy, the United Kingdom, and Greece, for a total of 971 ovarian cancer cases and 2,258 controls under age 65. Compared with never-users, the combined multivariate relative risk (RR) for ever-users was 0.6 (95% confidence interval, CI = 0.4-0.8) and the estimates were consistent in the 3 datasets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 27 publications
(49 reference statements)
5
57
1
1
Order By: Relevance
“…There is epidemiologic evidence that factors associated with fewer lifetime ovulations, such as pregnancy, lactation, or use of oral contraceptives, is associated with a marked decrease in OVAC risk. (2,(46)(47)(48)(49)(50). Although the mechanism responsible for this protective effect is not fully understood, the findings are supportive of the "incessant ovulation" hypothesis which states that the ovarian epithelium is subject to genetic damage during the wound and repair processes associated with ovulation (5).…”
Section: Discussionmentioning
confidence: 99%
“…There is epidemiologic evidence that factors associated with fewer lifetime ovulations, such as pregnancy, lactation, or use of oral contraceptives, is associated with a marked decrease in OVAC risk. (2,(46)(47)(48)(49)(50). Although the mechanism responsible for this protective effect is not fully understood, the findings are supportive of the "incessant ovulation" hypothesis which states that the ovarian epithelium is subject to genetic damage during the wound and repair processes associated with ovulation (5).…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methods have already been described. 12 Briefly, the first was a hospital-based investigation conducted in London and Oxford, UK, between 1978 and 1983. 17 Cases were 235 women under 65 years of age with epithelial ovarian cancer; controls were 451 women of comparable age, hospitalized for gastrointestinal diseases (23%), bone or joint diseases including fractures (22%) and a large number of other diagnostic categories, each including Ͻ10% of the total number of controls.…”
Section: Methodsmentioning
confidence: 99%
“…2,8 -11 A few studies, however, have assessed the risk with longer time since last use. [12][13][14][15][16] A cohort analysis of ovarian cancer incidence and mortality rates in U.S. women over the period 1970 -1995 7 indicated that the relative decrease in incidence is greater before age 50. There is, therefore, a suggestion that the protection declines with time since last use, but the data are inconclusive.…”
mentioning
confidence: 99%
“…That use of hormonal contraceptives (HC) may reduce the incidence of ovarian cancer is well established from both casecontrol (Weiss et al, 1981;Centers for Disease Control Cancer and Steroid Hormone Study, 1987; The WHO Collaborative Study of Neoplasia and Steroid Contraceptives, 1989;Franceschi et al, 1991;Whittemore et al, 1992;Siskind et al, 2000) and cohort studies (Ramcharan et al, 1980;Willett et al, 1981;Vessey et al, 1987;Beral et al, 1988Beral et al, , 1999Hankinson et al, 1995;Vessey and Painter, 1995), as recently reviewed (IARC Working Group, 1999;La Vecchia and Franceschi, 1999). Indeed, this benefit may be strong enough to reduce population-based incidence rates in places where HC have been used extensively (Adami et al, 1990;Parazzini et al, 2000;Walker et al, 2002).…”
mentioning
confidence: 99%